Revision of the genus Dinotoperla Tillyard, 1921 (Plecoptera: Gripopterygidae) using morphological characters and molecular data: Establishes two new genera, three new species and updates the larval taxonomy - Mynott, Julia H; Suter, Phillip J; Theischinger, Gunther (Zootaxa, 2017)
The larval taxonomy of Australian stoneflies (Plecoptera) shows a large disparity in knowledge when compared to the adult taxonomy with many species having undescribed larval forms. The importance of stoneflies as an indicator group for monitoring aquatic ecosystems means knowledge of the larval taxonomy and the ability to identify species is essential. This study combined morphology and mitochondrial gene sequences to associate the adult and larval life-stages for species of Dinotoperla Tillyard. Morphological identification of adult males was recognised for 17 of the 35 Dinotoperla species and combining molecular data with morphology confirmed eight new adult-larval life stage associations. Further, molecular data supported the larval taxonomy for five morphospecies which remain unassociated. The combination of molecular and morphological methods enabled the larval morphology to be reassessed for the genus Dinotoperla and this has led to the establishment of two new genera, Odontoperla, gen. nov. and Oedemaperla, gen. nov., and the new species Dinotoperla aryballoi, sp. nov, D. tasmaniensis, sp. nov. and Oedemaperla shackletoni, sp. nov. as well as the new or updated descriptions of the larvae of 31 species and a comprehensive dichotomous key to these larvae.